2022
DOI: 10.1016/j.jbc.2021.101435
|View full text |Cite
|
Sign up to set email alerts
|

A redox cycle with complex II prioritizes sulfide quinone oxidoreductase-dependent H2S oxidation

Abstract: The dual roles of H 2 S as an endogenously synthesized respiratory substrate and as a toxin raise questions as to how it is cleared when the electron transport chain is inhibited. Sulfide quinone oxidoreductase (SQOR) catalyzes the first step in the mitochondrial H 2 S oxidation pathway, using CoQ as an electron acceptor, and connects to the electron transport chain at the level of complex III. We have discovered that at high H 2 S concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
1
29
0
1
Order By: Relevance
“…In other organisms living in anaerobic or microaerophilic environments (e.g., E. coli [ 41 ], Mycobacterium tuberculosis [ 32 , 42 , 43 , 44 ], Ascaris suum (adult stage) [ 29 ], Echinococcus multilocularis (protoscoleces) [ 45 ], and even in several solid tumor cells [ 46 ]), the QFR activity of complex II is well documented and has been suggested to play an important role in environmental adaptation. Previously, we demonstrated that the disruption of the Fp subunit-encoding gene of P. falciparum ( sdha ) impairs the growth of blood-stage parasites; the growth of the Δsdha mutant was rescued by succinate but not by fumarate, suggesting that this plasmodial complex II might function as a QFR rather than as a SQR [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In other organisms living in anaerobic or microaerophilic environments (e.g., E. coli [ 41 ], Mycobacterium tuberculosis [ 32 , 42 , 43 , 44 ], Ascaris suum (adult stage) [ 29 ], Echinococcus multilocularis (protoscoleces) [ 45 ], and even in several solid tumor cells [ 46 ]), the QFR activity of complex II is well documented and has been suggested to play an important role in environmental adaptation. Previously, we demonstrated that the disruption of the Fp subunit-encoding gene of P. falciparum ( sdha ) impairs the growth of blood-stage parasites; the growth of the Δsdha mutant was rescued by succinate but not by fumarate, suggesting that this plasmodial complex II might function as a QFR rather than as a SQR [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among many mediators, H 2 S can induce such effects, for instance through persulfidation of protein cysteines or through its actions on metal-containing active centers [ 4 ]. For instance, in cancer cells, H 2 S has been shown to drive SQR-dependent respiration causing a reversal of the TCA cycle, glutamine deprivation, increased glycolysis and lipogenesis – effects that are not ultimately linked to altered expression of SQR protein [ 42 ]. In other cell types – e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically, SDHA maturation is critical for the correct functioning of mature CII. As CII is a master controller of metabolism that connects the Krebs cycle 36 with bioenergetics during aerobic respiration, oxygen limitation 37 or sulfide signaling 38 , SDHA maturation has broad physiological implications.…”
Section: Discussionmentioning
confidence: 99%